Comparison of E-Trust and Trust Concepts in Online and Offline Dimensions - Radionova-Girsa Elina; Lahiža Agnesa (Economics and Business)
In everyday lives, we more and more use different technology products to make our lives easier and faster. We often do not realise that we are switching our lifestyles to the online platform - we do everything mostly online - meet and communicate with others, watch videos and listen to favourite songs, choose and buy different things. The main question is - can we trust everything that we see on the screen? Is the explanation of “trust” the same in real life and in online sphere? Authors of the paper compare the concept of “trust” in offline trade market with that in online trading. The following methods were used - literature study and analysis, consumer survey and statistical analysis. Consumer survey is already in the process and is to be continued during the next 2 years with the purpose to compare changes through years. Participants of the survey are the inhabitants of Latvia of different age groups, location, profession, etc. The authors have continued the survey to make it more complete and to find out new tendencies. It is possible to use the research results in both ways ‒ theoretical and practical in respect of choosing an effective communication with consumers, in creating a long-term relationship with them, and in regard to increasing the customer loyalty level and level of “trust”.